2014
DOI: 10.1111/comt.12033
|View full text |Cite
|
Sign up to set email alerts
|

Advancing Warranting Theory

Abstract: Since its introduction by Walther and Parks (2002), warranting has emerged in the literature as a prominent construct that offers insight for understanding how online self-presentations are produced and evaluated. This manuscript outlines limitations that exist in the literature on warranting and provides suggestions for how the construct can be advanced theoretically and tested empirically. Notably, testable theoretical propositions are derived that specify how various factors are anticipated to affect percep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(97 citation statements)
references
References 47 publications
3
92
0
2
Order By: Relevance
“…Given that source characteristics can influence interpretations of online sexism (Strain et al, 2015), future research should also investigate how people interpret sources' interactivity with these messages. For example, users may make distinct attributions if a message is directly from the source or from another person and merely endorsed by the source (DeAndrea, 2014).…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%
“…Given that source characteristics can influence interpretations of online sexism (Strain et al, 2015), future research should also investigate how people interpret sources' interactivity with these messages. For example, users may make distinct attributions if a message is directly from the source or from another person and merely endorsed by the source (DeAndrea, 2014).…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%
“…This is the second opportunity for online daters to evaluate each other for a face-to-face meeting. Previous research on Warranting Theory has shown that online daters engage in private messaging as an interactive uncertainty reduction strategy to seek cues that they hope will "warrant" or authenticate information found in profile pages [6,12]. Yet despite their warranting efforts, users still find it difficult to validate experiential attributes through private messaging [38,39,40].…”
Section: Evaluation In Online Dating Systemsmentioning
confidence: 99%
“…It does so by focusing on an analysis of the costs and benefits of producing or interpreting a given signal. For the signal producer, the costs of deceptively producing a signal must outweigh the benefits of trying to fake it in order for the signal to be reliable (DeAndrea, 2014).…”
Section: Principles Of Signaling Theorymentioning
confidence: 99%
“…On the sender side, costs are associated with the effort to produce a signal as well as the potential consequences of being caught producing a misleading signal (for example, getting fired) (DeAndrea, 2014).…”
Section: Principles Of Signaling Theorymentioning
confidence: 99%
See 1 more Smart Citation